Relación entre los usos de suelo y la diversidad de macroinvertebrados acuáticos en el Estero El Barro de La microcuenca Baja del Río Quevedo - Macias Diaz, Darwin David (2021)
This research was carried out in the Barro estuary of the lower Quevedo River microbasin, where the structure of aquatic macroinvertebrates was evaluated as indicators of water quality, assessing the categories of agricultural, mining, urban, forest and pasture land use, with the purpose of determining the influence within the water bodies. For this purpose, the genera of aquatic macroinvertebrates were collected and identified in three sections of each category according to land use, the samples were deposited in labeled bottles of 70% alcohol, followed by the identification of genera in the laboratories of the UTEQ; in order to calculate the diversity of macroinvertebrate communities, using the Shannon, Simpson, Margalef and BMWP-Cr indexes. Also, the quality of bank indices (QBR) and fluvial quality (IHF) were estimated. In addition, eight physical-chemical parameters were defined to determine water quality (turbidity, hardness, pH, electrical conductivity, total dissolved solids, dissolved oxygen, temperature and salinity). A total of 1393 species were collected in agricultural, mining, urban, forest and pasture land uses, where 7 orders, 16 genera and 15 families were identified. The most representative genera were Pentaneura agricultural and urban, Baetodes mine, forest and pasture with minor, the genera Camelobaetidius, Lutzomyia and Camelobaetidius. The presence of the attributes in the sampling stations, were found in substrates of blocks, silt, stones and sands in fast, slow in shallow and deep habitats. The ANOVA statistical analysis showed that, by means of the Simpson index, there is a statistical difference between the macroinvertebrate community as opposed to the Shannon and Margalef indices in relation to soil use, showing that there is similarity between the diversity and heterogeneity of dominant species of aquatic macroinvertebrates. The riparian index in the forest and pasture categories showed a good quality, while the urban sector revealed a very poor quality. However, in the fluvial index, the most representative derivations are the forest, pasture and mine categories showing a moderate interpretation and the agricultural and urban categories showing a moderate to poor quality. Keywords: Water quality, river quality, bank index, physical-chemical parameters, Shannon, Simpson, Margalef and BMWP-Cr.